2022
DOI: 10.3390/toxics10030112
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Presentations of Nitrous Oxide Users in an Emergency Department

Abstract: Today, the concomitant abuse of nitrous oxide (N2O) and illicit drugs is evident and problematic. However, there are few reports regarding the clinical manifestations of N2O users when they present to the emergency department (ED). The purpose of this study was to describe the clinical presentations, the associated illicit substances used in combination, and the outcomes in N2O users visiting the ED. This was a retrospective observational cohort study. All N2O adult users admitted to the ED at Linkou Chang Gun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
2
0
1
Order By: Relevance
“…Selling and buying N 2 O tanks was legal in The Netherlands until recently but will be banned from January 1, 2023 [30]. Notably, we observed that the majority of patients with N 2 O intoxication used solely N 2 O, without concomitant drug or alcohol exposures, which has also been observed in other studies [1, 28, 31]. This is remarkable because most recreational drug intoxications reported to the DPIC concern poly-drug intoxications [32].…”
Section: Discussionsupporting
confidence: 84%
“…Selling and buying N 2 O tanks was legal in The Netherlands until recently but will be banned from January 1, 2023 [30]. Notably, we observed that the majority of patients with N 2 O intoxication used solely N 2 O, without concomitant drug or alcohol exposures, which has also been observed in other studies [1, 28, 31]. This is remarkable because most recreational drug intoxications reported to the DPIC concern poly-drug intoxications [32].…”
Section: Discussionsupporting
confidence: 84%
“…This is of serious concern because repeated exposure to high doses of N 2 O for a prolonged time is known to induce neurological damage, such as (irreversible) neuropathy and paralysis due to N 2 O-induced cobalamin deficiency [ 15 , 16 , 17 , 18 , 19 ]. The increasing trend of recreational users with N 2 O-induced neurological damage at emergency departments confirms the urgency of this development [ 9 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, it is imperative to understand and address the potential risks associated with prolonged inhalation of N₂O (3,4). Additionally, the increasing incidence of individuals presenting at emergency departments with neurological impairments due to N₂O exposure highlights the concerning and serious nature of this trend (5).…”
Section: Introductionmentioning
confidence: 99%